Virtual Anatomy Learning in a Medical College in Eastern Part of India during Pandemic - Nath, Sunandita; Ghosh, Satarupa Paul; Sinha, Sumita (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: The fundamental cornerstone of medical education is Anatomy which specially requires a 3D visualization of human body by traditional mode of teaching. During covid-19 pandemic it was forcefully stopped by introducing newer virtual teaching program. This had offered an opportunity to explore blending of newer methods with traditional one. To find effectiveness of online classes in anatomy during pandemic. And to find out whether online teaching hampers inter-personal relationship. Methods: Data obtained through questionnaire from 230 first year MBBS students’ responses at R.G. Kar Medical College and Hospital were recorded and analysed. Results: 50% of the students were in favour of virtual learning process, 34% were satisfied with online mode as independent mode of learning, 61% responded that online teaching will be helpful for the advancement of their career. Conclusions: The pre-recorded online demonstration classes are better appreciated by the students than hand role playing (which is important in NMC criteria) online classes. Some topics are better taught through online mode than offline method.